Modelling of flood hazard using topographic wetness index in Yeh Ho Watershed, Bali, Indonesia - Adnyana I Made; Wiguna Putu Perdana Kusuma (BIO Web of Conferences)
Topography is an essential control in the spatial distribution of flood events. Topographic Wetness Index (TWI) is a method of quantifying topographic control of hydrological processes. This research aims to determine the spatial distribution of flood hazard areas using the TWI method in the Yeh Ho watershed, one of the largest watersheds in Bali Province, Indonesia. The flood hazards are then classified as low, medium, and high hazard. The result shows that T, The low hazard class, has a distribution area of 9630.26 ha (58.3% of total hazard area), while the medium hazard class has an area of 4802.66 ha (29.1%), and the high hazard class has a distribution area of 2083.10 ha (12.6%). The areas of Penebel and Selemadeg Timur Districts have areas with moderate and high hazard classes, respectively 2,190.65 ha (13.26%) and 1,154.35 ha (6.99%). Meanwhile, Selemadeg Timur has areas with moderate and high hazard classes, respectively 2,179.74 ha (13.20%) and 802.33 ha (4.86%). The TWI method can be used to carry out flood rapid assessments. More detailed DEM data resolution and other flood parameter data such as rainfall and soil type are needed to carry out more detailed flood modelling.